Iridoid and Furanolabdane -Type Diterpene Glycosides from Rhizomes of Eremostachys azerbaijanica Rech. f. - Solmaz Asnaashari*; Abbas Delazar; Sedigheh Bamdad Moghaddam (Iranian Society of Pharmacognosy, 2018)
Background and objectives: The rhizomes of Eremostachys azerbaijanica Rech. f.,as an indigenous plant in East Azerbaijan province of Iran, were studied for isolation and identification of possible phytoconstituents. Methods: The air- dried and ground rhizomes were extracted with n-hexane, dichloromethane (DCM) and methanol (MeOH) using a Soxhlet apparatus. The 10%, 20% and 80% MeOH in water C18 cartridge solid phase extraction products )Sep-Pak fractions( of the MeOH extract were subjected to preparative reversed- phase high performance liquid chromatography (RP-HPLC) and the isolated pure compounds were identified by one- dimensional nuclear magnetic resonance (1D-NMR) spectroscopic technique. Results: The spectroscopic data of the compounds were compared with the respective published data and the obtained results showed the presence of four pure components, 6 - Hydroxy loganin (1), Shanzhiside methyl ester (2), Eremostachiin (β-D-glucopyranosyl-(1→2)-β-D-glucopyranosyl ester of phlomisoic acid) (3) and  Phlomisoside II (4), with iridoid and furano labdane- type diterpene glycoside structures. Conclusion: The occurrence of these types of chemical structures might be a confirmation to close relation and similar pharmacological and biological activities between Eremostachys and Phlomis genera.